On the Need of the Wavelet Analysis for Fatigue Condition Monitoring - N., Ismail; M. F. M., Yusof; C. K. E., Nizwan; S., Abdullah (2015)
Wavelet analysis has attracted attention for its ability to analyse rapidly changing transient signals. Based on that capability, it was then used in this study to detect high amplitude of strain signal of the coil spring. The signals were recorded at two different road profiles that are paved road and unpaved road. Wavelet analysis was then performed in order to obtain wavelet transform representation for each of the road. Fatigue damage assessment will be used to verify this finding. The obtained result shows that the time of peaks occurrence in wavelet transform representation are in line with the time of the high amplitude strain occurrence. It is true for all types of signal. It is also verified with the value of the fatigue damage. It is noticed that the value of the fatigue damage is higher at the similar time frame. The finding indicates that the wavelet analysis can be used as an alternative method for the fatigue condition monitoring cases.